2014
DOI: 10.1002/adma.201304912
|View full text |Cite
|
Sign up to set email alerts
|

25th Anniversary Article: Label‐Free Electrical Biodetection Using Carbon Nanostructures

Abstract: Nanostructures are promising candidates for use as active materials for the detection of chemical and biological species, mainly due to the high surface-to-volume ratio and the unique physical properties arising at the nanoscale. Among the various nanostructures, materials comprised of sp(2) -carbon enjoy a unique position due to the possibility to readily prepare them in various dimensions ranging from 0D, through 1D to 2D. This review focuses on the use of 1D (carbon nanotubes) and 2D (graphene) carbon nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
97
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 193 publications
1
97
0
3
Order By: Relevance
“…Interestingly, various atomic hybrid orbitals were observed, including sp, sp 2 , and sp 3 characteristics 1. Moreover, the anisotropy of crystal and other arrangements are dominated by that of sp 2 , giving rise to the innumerable characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, various atomic hybrid orbitals were observed, including sp, sp 2 , and sp 3 characteristics 1. Moreover, the anisotropy of crystal and other arrangements are dominated by that of sp 2 , giving rise to the innumerable characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…field-effect transistor | Debye screening | surface modification | DNA aptamer receptor | polyethylene glycol N anoelectronic biosensors offer broad capabilities for label-free high-sensitivity real-time detection of biological species that are important to both fundamental research and biomedical applications (1)(2)(3)(4)(5)(6). In particular, field-effect transistor (FET) biosensors configured from semiconducting nanowires (1,2), single-walled carbon nanotubes (1,3,4), and graphene (1,5,6) have been extensively investigated since the first report of real-time protein detection using silicon nanowire devices (7).…”
mentioning
confidence: 99%
“…In particular, field-effect transistor (FET) biosensors configured from semiconducting nanowires (1,2), single-walled carbon nanotubes (1,3,4), and graphene (1,5,6) have been extensively investigated since the first report of real-time protein detection using silicon nanowire devices (7). Subsequent studies have demonstrated highly sensitive and in some cases multiplexed detection of key analytes, including protein disease markers (8-10), nucleic acids (11)(12)(13), and viruses (14), as well as detection of protein-protein interactions (8,(15)(16)(17) and enzymatic activity (8).…”
mentioning
confidence: 99%
“…b) Medidas de potencial de eletrodo do grafeno na ausência da BOx, na presença da enzima imobilizada no eletrodo em Ar saturado (linha pontilhada azul) e em O 2 saturado (linha sólida azul). c) A cronoamperometria do eletrodo de grafeno (em preto) e do eletrodo de grafeno com a enzima BOx imobilizada (em azul) mostra o comportamento da densidade de corrente após a injeção de gás oxigênio no meio eletrolítico e a estabilidade durante 40 Figura 29 -a) Curvas de polarização do bioânodo (em vermelho) e do biocátodo (em azul) em O 2 saturado na presença dos respectivos substratos (linhas sólidas) e na ausência dos substratos (linhas pontilhadas). Velocidade de varredura: 2 mV s -1 .…”
Section: Lista De Figurasunclassified
“…A obtenção de dispositivos portáteis é muito interessante do ponto de vista científico e tecnológico [38][39][40] . O desenvolvimento de estratégias que permitam a obtenção de sistemas miniaturizados, como os dispositivos em um único chip, vem acompanhados da necessidade de desenvolvimento de novas tecnologias 41,42 .…”
Section: Dispositivos On-chipunclassified